2016
DOI: 10.1103/physrevlett.117.023601
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Absorption of N00N States

Abstract: Recent results in deeply subwavelength thickness films demonstrated coherent control and logical gate operations with both classical and single photon light sources. However, quantum processing and devices typically involve more than one photon and non-trivial input quantum states. Here we experimentally investigate two-photon N00N state coherent absorption in a multilayer graphene film. Depending on the N00N state input phase, it is possible to selectively choose between single or two photon absorption of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…Depending on the phase relation of the input N00N state, one can deterministically obtain either a single photon state or a mixture of zero and two photon states at the output. This phenomenon has been coined quantum nonlinear absorption and has been observed in a recent experiment [14]. In this setup, evidence of being in such a coherent absorption regime is given by the reminiscent single plasmon oscillations shown in figure 5.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Depending on the phase relation of the input N00N state, one can deterministically obtain either a single photon state or a mixture of zero and two photon states at the output. This phenomenon has been coined quantum nonlinear absorption and has been observed in a recent experiment [14]. In this setup, evidence of being in such a coherent absorption regime is given by the reminiscent single plasmon oscillations shown in figure 5.…”
Section: Discussionmentioning
confidence: 78%
“…While a lossless beamsplitter imposes a constrained phase relationship between r and t, namely r=±it, a lossy beamsplitter can be designed to exhibit any different phase relation. It has been theoretically and experimentally shown that new quantum effects arise for the case r=±t [10,13,14]. Depending on the phase relation of the input N00N state, one can deterministically obtain either a single photon state or a mixture of zero and two photon states at the output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Recently, exotic properties of lossy beam splitters, such as apparent nonlinear absorption, 36 have attracted the attention of the nanophotonics community. 29,37 As illustrated by Fig. 1(a), the interaction of two coherent beams of equal intensity on an "ideal" lossy beam splitter results in two output beams of equal intensity.…”
Section: -4mentioning
confidence: 99%
“…However, such detectors often exhibit poor performance (primarily in terms of sensitivity and fall times, which affects the sampling rate), and currently the majority of quantum optics experiments are carried out with click detectors. One possible avenue for optical QST with click photodetectors is to mimic their functionality by the addition of beamsplitters 64 . However, this method introduces further losses to the system and is not scalable to larger number of channels and photons.…”
mentioning
confidence: 99%